Risk Factors for Legionella longbeachae Legionnaires’ Disease, New Zealand - Kenagy, Emma; Priest, Patricia C.; Cameron, Claire M.; Smith, Debbie; Scott, Pippa; Cho, Vicki; Mitchell, Peter; Murdoch, David R. (Emerging infectious diseases, 2017)
Legionella longbeachae, found in soil and compost-derived products, is a globally underdiagnosed cause of Legionnaires' disease. We conducted a case-control study of L. longbeachae Legionnaires' disease in Canterbury, New Zealand. Case-patients were persons hospitalized with L. longbeachae pneumonia, and controls were persons randomly sampled from the electoral roll for the area served by the participating hospital. Among 31 cases and 172 controls, risk factors for Legionnaires' disease were chronic obstructive pulmonary disease, history of smoking >10 years, and exposure to compost or potting mix. Gardening behaviors associated with L. longbeachae disease included having unwashed hands near the face after exposure to or tipping and troweling compost or potting mix. Mask or glove use was not protective among persons exposed to compost-derived products. Precautions against inhaling compost and attention to hand hygiene might effectively prevent L. longbeachae disease. Long-term smokers and those with chronic obstructive pulmonary disease should be particularly careful.